2004
DOI: 10.1063/1.1781625
|View full text |Cite
|
Sign up to set email alerts
|

Study of hard x-ray emission from intense femtosecond Ti:sapphire laser–solid target interactions

Abstract: Interaction of intense Ti:sapphire laser with solid targets has been studied experimentally by measuring hard x-ray and hot electron generation. Hard x-ray ͑8 -100 keV͒ emission spectrum and K␣ x-ray conversion efficiency ͑ K ͒ from plasma have been studied as a function of laser intensity ͑10 17 -10 19 W/cm 2 ͒, pulse duration ͑70-400͒fs, and laser pulse fluence. For intensity I Ͼ 1 ϫ 10 17 W/cm 2 , the Ag K increases to reach a maximum value of 2 ϫ 10 −5 at an intensity I =4 ϫ 10 18 W/cm 2 . Hot electron tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 42 publications
1
46
1
Order By: Relevance
“…Fast electron spectrum shows a peaked structure and it is suitable for Cu Kα photon generation, considering Cu K-shell ionization cross section. The spectrum cannot be fitted by Maxwellian distribution for a temperature because the laser pulse is too short to cause plasma satisfied to local thermal equilibrium [12]. It should be noted that there is an individual second peak with energy ~ 110 keV in case of P-polarized laser irradiation, which means another group of quasi monoenergetic electron heated by other mechanism and contribute enhancement of fast electron and Kα photon generation in this case.…”
Section: Figure 2(a)mentioning
confidence: 99%
See 2 more Smart Citations
“…Fast electron spectrum shows a peaked structure and it is suitable for Cu Kα photon generation, considering Cu K-shell ionization cross section. The spectrum cannot be fitted by Maxwellian distribution for a temperature because the laser pulse is too short to cause plasma satisfied to local thermal equilibrium [12]. It should be noted that there is an individual second peak with energy ~ 110 keV in case of P-polarized laser irradiation, which means another group of quasi monoenergetic electron heated by other mechanism and contribute enhancement of fast electron and Kα photon generation in this case.…”
Section: Figure 2(a)mentioning
confidence: 99%
“…resonant absorption maybe non-effective with femtosecond laser-dense plasma interactions [12], whereas high contrast laser is more efficient for hard x-ray generation via enhanced "vacuum …”
Section: Figure 4(b)mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, we have demonstrated a kilohertz Cu K␣ source produced by submillijoule laser pulses 20 where the x-ray conversion to Cu K␣ x-ray emission was comparable to that using multimillijoule laser pulses. [21][22][23] The higher conversion efficiency was achieved by optimizing the laser intensity and prepulse on a solid rotating copper target. 20,24 An optimized scale length of less than a wavelength has been demonstrated in a recent study because of the transition from resonance absorption to vacuum heating in this intensity regime.…”
mentioning
confidence: 99%
“…For applications development, recent progress of laser systems combining high intensity and high repetition rate have attracted considerable interest for the production of solid target based secondary sources where high mean brightness is required. In high field science, this includes bright x-ray sources (Chen et al, 2004;Schnürer et al, 2000;Teubner et al, 2003;Thaury et al, 2007), high energy particle acceleration (Fritzler et al, 2003;Steinke et al, 2010;Zeil et al, 2010) and nuclear activation (Grillon et al, 2002;Magill et al, 2003). To illustrate this interest for high peak intensities, recently published scaling laws for laser based proton acceleration on thin film solid targets (Fuchs et al, 2006) have shown that an important increase of the on target laser intensity is necessary to reach the expected energy required for biomedical application in the proton therapy field (60 -250 MeV).…”
Section: Introductionmentioning
confidence: 99%